Effect of stakeholders' perceptions on the relationship between quality of public universities and graduate employability in Malaysia - Almasri, Amal (2021)
Employability is considered the key factor in the link between higher education institutions and the labor market in providing qualified and competent graduates for the employment markets. In Malaysia, most of the public universities have achieved the accredited levels of quality to run the academic programs based on the requisite standards. However, the rate of unemployment among graduates is considered high, which has affected the institutions' reputation. On the other hand, there are reports that some employers consider Malaysian graduate competencies do not meet the expectations of the workplace. Therefore, this study was conducted to determine whether the quality of public universities would influence graduate employability in the presence of graduate competencies as a mediating variable. The graduates and employers were considered as the key and most relevant stakeholders to provide the required information to achieve the research objectives. This study adopted human capital theory as the underpinning theory for its proposed conceptual framework. Based on a post-positivism paradigm, this study employed a mixed-method triangulation design which is both quantitative and qualitative methods to obtain data on the perceptions of graduates and employers as the stakeholders of higher education institutions. Data was collected from 483 graduates from three selected public universities (UPM, UM, and UKM) through a self-administered questionnaires survey. Structural Equation Modelling (SEM) was employed to investigate the study's structural model by using AMOS. This study is strengthened by ten personal interviews with employers as the qualitative data to support the quantitative results. The findings of this study prove that employers' perceptions have supported the graduates’ responses, where the determinants of university quality, including reputation, academic program and curriculum, infrastructure and support facilities, academic staff, and training are the influential factors on graduate competencies and employability. ii The main theoretical contribution is on the aspect of determinants of the quality in public universities, graduate competencies, and graduate employability are concomitant in one comprehensive framework. In addition to that, the relevant authorities and institutions in higher education sectors should pay particular attention to the skills and competencies required by employers to produce the ever-equipped and future-proof graduates.